The Use of Cupressus arizonica as a Biomonitor of Li, Fe, and Cr Pollution in Kastamonu - Cesur, Alican; Zeren Cetin, Ilknur; Cetin, Mehmet; Sevik, Hakan; Ozel, Halil Baris (Springer Science and Business Media LLC, 2022)
Air pollution became an important problem that severely threatens human health, especially in urban areas. Such that it was reported that 90% of global population respire polluted air and the air pollution causes the death of approx. 7 million annually. It is known that heavy metals have a significantly high share in these deaths. Heavy metals are elements, which do not easily disintegrate in nature, can accumulate in bodies of living organisms, and can be toxic, carcinogenic, and even lethal. Thus, monitoring the changes of heavy metal concentrations in the air is very important for human and environmental health. The method most preferred for determining the change of heavy metal concentration in the atmosphere is the biomonitors. The use of annual rings of trees is one of the most accurate methods because they can provide information about the long-term change of heavy metal concentrations in the air. In the present study, it was aimed to reveal the usability of annual rings of Cupressus arizonica as a biomonitor in determining the change of Li, Fe, and Cr concentrations. Within the scope of this study, the concentrations of elements in the inner bark, outer bark, and wood in the roadsides, where there is intense traffic, and opposite sides of trees were compared and the annual changes in heavy metal concentrations in annual rings were investigated. At the end of this study, it was determined that Fe and Cr concentrations in the roadside outer barks of trees were generally at very high levels, that the annual changes of elements generally followed a fluctuating course, and that annual rings of Cupressus arizonica are very useful for monitoring the annual change of Fe concentration in the air but not for monitoring the changes in Li and Cr concentrations. Scientific and Technological Research Council of Turkey (TUBITAK); Turkish Council of Higher Education (YOK); Bartin University [YOK 100/2000] The Scientific and Technological Research Council of Turkey (TUBITAK), Turkish Council of Higher Education (YOK), Bartin University: YOK 100/2000 PhD Scholarship.
Keywords: Annual Ring; Heavy Metal; Biomonitor; Cupressus Arizonica; Pollution; 13. Climate action; 11. Sustainability; 3. Good health